Penyuluhan Masyarakat Mojogede Pada Pemanfaatan Minuman Fungsional Kombinasi Jahe dan Serai - Janatun Na'imah; Heru Baskoro; Anindi Lupita Nasyanka (Universitas Mataram, 2020)
Coronavirus Disease 2019 (Covid-19) is a new type of disease that has never been identified before in humans. The virus that causes Covid-19 is called Sars-CoV-2. This research was conducted to educate the public about the use of ginger and lemongrass functional drinks to improve immunity. The method of implementing Community Service is carried out interactively with a video conversion application ZOOM on 25 youth cadets in the village of Mojogede, Balongpanggang Gresik on June 14, 2020. Before starting the event the participants were given a face shield that must be used during the event as an effort to implement health protocols. Furthermore, pre-test is given first, then material exposure is carried out and continued filling in post-test with the same problem. Based on the results of the pre-test and post-test obtained an increase in public knowledge which was 79.09% to 89.23%.